2020
DOI: 10.18632/oncotarget.27799
|View full text |Cite
|
Sign up to set email alerts
|

MEK inhibitors reduce cellular expression of ACE2, pERK, pRb while stimulating NK-mediated cytotoxicity and attenuating inflammatory cytokines relevant to SARS-CoV-2 infection

Abstract: COVID-19 affects vulnerable populations including elderly individuals and patients with cancer. Natural Killer (NK) cells and innate-immune TRAIL suppress transformed and virally-infected cells. ACE2, and TMPRSS2 protease promote SARS-CoV-2 infectivity, while inflammatory cytokines IL-6, or G-CSF worsen COVID-19 severity. We show MEK inhibitors (MEKi) VS-6766, trametinib and selumetinib reduce ACE2 expression in human cells. In some human cells, remdesivir increases ACE2-promoter luciferase-reporter expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 55 publications
2
31
0
Order By: Relevance
“…MEK inhibitors have known antiviral efficacy against coronaviruses, inhibiting the Raf/MEK/ERK signaling pathway and impairing viral production but not viral entry into the cell in a murine coronavirus hepatitis virus model 66 . It was recently shown that selumetinib, like trametinib, a MEK inhibitor also identified in this study, can stimulate natural killer cells, reduce ACE2 expression in human cells, and reduce cytokine expression in COVID-19 patient plasma, suggesting that this class of drugs may both suppress infection by SARS-CoV-2 and support the body’s immune response to infection 39 . Overall, our approach acts a useful screen for identifying common candidate drugs to reverse gene signatures for SARS-CoV-2 infected tissues despite the differences in disease transcriptome profiles from different data sources.…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…MEK inhibitors have known antiviral efficacy against coronaviruses, inhibiting the Raf/MEK/ERK signaling pathway and impairing viral production but not viral entry into the cell in a murine coronavirus hepatitis virus model 66 . It was recently shown that selumetinib, like trametinib, a MEK inhibitor also identified in this study, can stimulate natural killer cells, reduce ACE2 expression in human cells, and reduce cytokine expression in COVID-19 patient plasma, suggesting that this class of drugs may both suppress infection by SARS-CoV-2 and support the body’s immune response to infection 39 . Overall, our approach acts a useful screen for identifying common candidate drugs to reverse gene signatures for SARS-CoV-2 infected tissues despite the differences in disease transcriptome profiles from different data sources.…”
Section: Resultssupporting
confidence: 52%
“…** Also identified in 2 different COVID-19 patient datasets. Drug Drug class Antiviral properties Trametinib Kinase inhibitor MERS-CoV 38 , SARS-CoV-2 39 Withaferin A Steroidal lactone SARS-CoV-2 40 – 43 Parthenolide Sesquiterpene lactone SARS 44 Lapatinib Kinase inhibitor SARS-CoV-2 45 Sorafenib Kinase inhibitor SARS-CoV-2 46 Auranofin Gold salt SARS-CoV-2 47 Selumetinib** Kinase inhibitor SARS-CoV-2 39 Erlotinib Antineoplastic, tyrosine kinase inhibitor HCV, RNA viruses, dengue, Ebola 48 50 Alvocidib CDK Inhibitor HSV, HIV, Flu 51 – 56 Quinacrine Antimalarial EMCV, poliovirus 57 Vandetanib Kinase inhibitor Andes virus 57 Dasatinib SRC tyrosine kinase inhibitor HIV 58 , 59 Thioridazine Phenothiazine …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies should be conducted to clarify the mechanistic role that these cytokines and macrophages play in the various stages of COVID-19 and correlate them with other hematologic parameters that were not collected in this database. The results of these future studies could identify more targeted immunomodulatory strategies beyond steroid administration such as treatment with MEK inhibitors ( Zhou et al, 2020 ), as well as the ideal timing of these interventions to maximize therapeutic efficacy. Future studies could also address the size limitations of this study, which was not powered to explore race- or ethnicity-related differences in COVID-19 severity.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies should be conducted to clarify the mechanistic role that these cytokines and macrophages play in the various stages of COVID-19. The results of these future studies could identify more targeted immunomodulatory strategies beyond steroid administration such as treatment with MEK inhibitors 13 , as well as the ideal timing of these interventions to maximize therapeutic efficacy. Finally, we present the application of this mutual information algorithm as a way to evaluate the dataset as a whole and elucidate the most important cytokines in predicting presenting severity of COVID-19.…”
Section: Discussionmentioning
confidence: 99%